Conceptual foundations of transmedia in the information space - Yessenbekova, Ұ.М.; Kutym, Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The article discusses the conceptual foundations of transmedia and new forms of communication. Directions and ways of disseminating transmedia technologies and new media have been identified. The evolution of the theoretical concepts of transmedia and the stages of development are studied in the telecommunication sphere. The recommendations are formulated for improving the information and communications industry and increasing its potential. The trends are studied in the market of transmedia technologies, the form of transmedia, the importance of the transmedia strategy, its influence on the audience, the place of advertising in the media activity. The author used different methodologies for determining and predicting the ways of development of transmedia technologies. The possibility of improving the effectiveness of transmedia communications are argued, taking into account the peculiarities of the national audience,. Under these conditions, transmedia technologies can effectively serve the interests of society